2020
DOI: 10.1101/2020.09.25.20200329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Uses CD4 to Infect T Helper Lymphocytes

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the agent of a major global outbreak of respiratory tract disease known as coronavirus disease-2019 (COVID-19). SARS-CoV-2 infects the lungs and may cause several immune-related complications such as lymphocytopenia and cytokine storm which are associated with the severity of the disease and predict mortality . The mechanism by which SARS-CoV-2 infection may result in immune system dysfunction is not fully understood. Here we show that SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 50 publications
1
46
0
2
Order By: Relevance
“…There is emerging evidence of cytokine over-production, in particular IL-6 and IL-10, as part of immunopathogenesis within COVID-19; however, drivers of these observed changes are still not fully understood. A recent pre-print report from a Brazilian research group describes infection of CD4+ T cells by SARS-CoV-2, with subsequent high expression of IL-10 by infected cells [ 79 ]. If these data are robust to peer-review and can be replicated elsewhere, this finding may represent one of the contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence of cytokine over-production, in particular IL-6 and IL-10, as part of immunopathogenesis within COVID-19; however, drivers of these observed changes are still not fully understood. A recent pre-print report from a Brazilian research group describes infection of CD4+ T cells by SARS-CoV-2, with subsequent high expression of IL-10 by infected cells [ 79 ]. If these data are robust to peer-review and can be replicated elsewhere, this finding may represent one of the contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, recent histopathological case studies from post-mortem COVID-19 patient tissues have reported the reactivity of SARS-CoV2 spike protein antibody in tracheal submucosa lymphocytes and alveolar macrophages [ 30 ], with observations of the splenic and lymph node regions of severe COVID patients have shown significant lymphocytic apoptosis, and SARS-CoV2 nucleoprotein reactivity along with IL-6 upregulation in ACE2 positive macrophages [ 31 ]. A recent study has confirmed SARS-CoV2 can directly infect and replicate in CD4 T helper cells via viral infection tests of isolated healthy human peripheral blood samples, and by confirming presence of SARS-CoV2 RNA in COVID patients [ 32 ]. However, these studies have not confirmed the expression of LFA-1 or Mac-1 in the SARS-CoV2-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently proposed that SARS-CoV-2 may be able to infect TH cells by the interaction between S protein and CD4 [ 119 ]. SARS-CoV-2 infected TH cells secrete higher levels of IL-10 and lower proinflammatory cytokines e.g., IFN-γ and IL-17, which is more pronounced in severe cases than in moderate cases or in healthy individuals.…”
Section: Immune Response To Sars-cov-2mentioning
confidence: 99%